Copy number variation regions in Nellore cattle: Evidences of environment adaptation - Antunes de Lemos, Marcos Vinicius [UNESP]; Berton, Mariana Piatto [UNESP]; Ferreira de Camargo, Gregório Miguel; Peripolli, Elisa [UNESP]; de Oliveira Silva, Rafael Medeiros [UNESP]; Ferreira Olivieri, Bianca [UNESP]; Cesar, Aline S.M.; Pereira, Angélica Simone Cravo; de Albuquerque, Lucia Galvão [UNESP]; de Oliveira, Henrique Nunes [UNESP]; Tonhati, Humberto [UNESP]; Baldi, Fernando [UNESP] (Elsevier, 2018)
The aim of the present study was to analyze the distribution of CNV regions (CNVRs) as well as to address hypothesis about the natural/artificial selection process in Nellore cattle. A total of 399,361 CNVs were identified, using the PennCNV algorithm, in 3794 Nellore cattle (Bos taurus indicus) genotyped with the Bovine HD BeadChip array. The default quality control was applied and 2902 samples and 195,873 CNVs remained. The medium CNV length size was 54,744 bp with a maximum of 870,000 bp and a minimum of 3000 bp. The CNVRs were generated by overlapping the 195,873 identified CNVs using the CNVRuler program. There was a higher incidence of CNVRs on BTA19 (24.26%), BTA23 (18.68%), and BTA25 (18.05%). The chromosomes that showed a lower incidence of CNVR were BTA29 (1.63%), BTA13 (9.72%), and BTA8 (9.72%). According to the type, 38.5%, 28.5% and 33.0% of the CNVRs were characterized as insertion, deletion and mixed (insertion and deletion in the same region), respectively. The 9805 CNVR estimated in the present study covered approximately 13.05% of the cattle genome (UMD_3.1, 2,649,685,063 bp) and overlapped with 5495 genes. These genes have functions described as involved in biological processes that might be related to the environmental adaptation of the subspecies to tropical areas, such as regulation of vasodilatation, immune system response, hair follicle morphogenesis, among others. This study confirms the existence of large structural variations in the Nellore cattle genome and contributes to understanding the differences between cattle subspecies. Besides, it can also work as a guideline for future studies in which structural variations are present.
Keywords: CNVR; Natural selection; Nellore; Structural variation; Subspeciation